2003
DOI: 10.1155/s1110662x03000370
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies of Ln(III) complexes with polyoxometalates in solids, and aqueous and non‐aqueous solutions

Abstract: Chosen polyoxometalate (POM) anions and their lanthanide(III) complexes, LnPOM, have been synthesized and spectroscopically characterized in solid state, aqueous and non-aqueous solutions. POMs, such as Keggin's, Dawson's and Anderson's type,Na9EuW10O36, compositions that function as inorganic cryptands ([(Na)P5W30O110]14−-Preyssler anion, and [(Na)As4W40O140]27−), containing inorganic(Na+,K+,NH4+)or organic (tetrabutylammonium,NBu4+) counter cations were obtained and their Ln(III) complexes (sandwiched and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The Eu(III) luminescence lifetimes, measured both for solids and non-aqueous solvents (CH 3 CN, DMF), indicate that the tetrabutylammonium salt of the Preyssler Eu(III) encrypted complex has a smaller number of water molecules in the Eu((III) inner coordination sphere [34] than the potassium compound [12]. This observation confirms also a higher luminescence quantum yield measured for NBuEuP 5 W 30 in acetonitrile (1.1 × 10 −4 ) in comparison to that obtained for K 12 [EuP 5 W 30 O 110 ] in water solution (9.6×10 −5 ) [18]. These results indicate that one or two water molecules not completely encrypted in the heteropolyanion, is/are expelled from vacancy during the extraction procedure.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…The Eu(III) luminescence lifetimes, measured both for solids and non-aqueous solvents (CH 3 CN, DMF), indicate that the tetrabutylammonium salt of the Preyssler Eu(III) encrypted complex has a smaller number of water molecules in the Eu((III) inner coordination sphere [34] than the potassium compound [12]. This observation confirms also a higher luminescence quantum yield measured for NBuEuP 5 W 30 in acetonitrile (1.1 × 10 −4 ) in comparison to that obtained for K 12 [EuP 5 W 30 O 110 ] in water solution (9.6×10 −5 ) [18]. These results indicate that one or two water molecules not completely encrypted in the heteropolyanion, is/are expelled from vacancy during the extraction procedure.…”
Section: Resultssupporting
confidence: 64%
“…The highest intensity and quantum yield was obtained for NBuEuPW 11 (similarly for potassium salt of this complex in aqueous solution [14,18]) after excitation at 394 nm. However, in the DMF solution an important role bring the charge-transfer band (320-340 nm) present in mixed tungstomolibdate complexes [14][15][16].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, stability study in temperature and under UV irradiation showed larger thermal and photochemical degradation compared with the systems with lower organic content. Similar studies have been conducted involving Eu 2 [TeMo 6 O 24 ] and [EuW 10 O 36 ] 9À anions and the resulting materials showed enhanced emission intensity and luminescence quantum yield compared with the corresponding POM in solution [51,52].…”
Section: Lanthanide-doped Pomssupporting
confidence: 68%